Authentication of honeys from Caramulo region (Portugal): Pollen spectrum, physicochemical characteristics, mineral content, and phenolic profile. Issue 2 (27th January 2020) - Silva, Luís R.; Gonçalves, Ana C.; Nunes, Ana R.; Alves, Gilberto
Abstract : Abstract: This study aimed to analyze the botanical origin, quality parameters, phenolic compounds, and minerals of 20 honey samples from Caramulo region (Portugal). Six samples were monofloral from Eucalyptus sp., being this one the predominant pollen in the analyzed samples, followed by Castanea sativa . The average values obtained for the physicochemical parameters were as follows: 4.7 pH; 16.8% moisture; 81.4 Brix; 0.3% ash; 512.8 µS/cm electrical conductivity; 22.6 meq/kg free acidity; 12.4 meq/kg lactonic acidity; 35.1 meq/kg total acidity; 2.1 mg/kg hydroxymethylfurfural; and 16.3 °Gothe for diastase activities. A total of 18 phenolics were determined by high‐performance liquid chromatography–diode array detector. Hydroxycinnamic acid derivatives and protocatechuic acid were the major ones. Nine minerals were detected by atomic absorption spectrometry; potassium and phosphorus were the predominant mineral elements. This is the first study about honeys from Caramulo region, which revealed to have a good quality and be a rich source of essential minerals and phenolics. Practical Application: The interest in the analysis of honey has increased significantly in recent years, concerning its characterization, safety implications, and health impact. Given these facts, the authentication of honeys, based on the geographical and botanical origins, has been assuming great importance, being mainly associated with high‐quality honeys. Therefore, we decided to analyze physicochemical parameters, phenolic composition, and mineral content of 20 Caramulo honey samples. Our results indicate that Caramulo honeys possess high‐quality levels, good freshness, maturity, and proper processing, and are also rich in several bioactive substances with health‐promoting properties, including phenolic compounds, potassium, and phosphorus.